A process for the hydrocarbonylation of amides

CN118005560BActive Publication Date: 2026-10-16CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211328822.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2026-10-16
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

但是反应过程仍然使用强碱,操作条件苛刻,且极易对环境造成污染

Benefits of technology

[0078] Through the above technical solution, this disclosure provides a method for amide hydrocarbonation, which enables amide hydrocarbonation reactions in heterogeneous, non-toxic solvent systems. The reaction process does not require the use of toxic or harmful solvents, and high amide conversion and selectivity can be obtained under mild reaction conditions, making it highly valuable for industrial applications. The catalyst used includes a hierarchical porous titanium-silicon molecular sieve, incorporating titanium atom active centers to enhance its resistance to deactivation. Furthermore, the molecular sieve has a multi-cavity structure within its crystals, containing abundant silanol active centers. This multi-cavity structure provides numerous independent reaction units, and the concentrated distribution of silanol active centers allows the molecular sieve to simultaneously possess… It possesses both acid and Lewis acid properties, along with a large specific surface area and pore volume, which is beneficial for efficient catalytic reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118005560B_ABST
    Figure CN118005560B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a method for amide hydrocarbylation, which comprises the following steps: contacting an amide compound, a hydrocarbyl alcohol and a catalyst to perform an amide hydrocarbylation reaction; wherein the catalyst comprises a hierarchical pore titanium silicalite molecular sieve; the hierarchical pore titanium silicalite molecular sieve has a plurality of cavity structures in the crystal. The method adopts a non-toxic solvent heterogeneous catalytic system, the catalyst has high catalytic activity and good chemical stability, and can efficiently catalyze the amide hydrocarbylation reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of organic chemical engineering, and specifically to a method for amide hydrocarbonation. Background Technology

[0002] The alkylation of amides refers to the nucleophilic substitution reaction between the amino nitrogen atom and the carbonyl oxygen atom in the amide and the alkylating agent, resulting in N-alkylated and O-alkylated amide molecules. N-alkylation of amides is widely used in the synthesis of pharmaceuticals and daily chemical products, such as Cerebrolysin, Phthalate, and Lauryl Azone, which are N-alkyl-substituted amides, imides, and lactams. The methylation products of amides and lactams, especially N-methylcaprolactam, are increasingly used as novel solvents in organic synthesis.

[0003] The N-alkylation of amides is generally carried out under alkaline conditions using haloalkanes as alkylating agents. Traditional methods employ strong bases (such as sodium alkoxides, sodium amides, and sodium hydride) as condensing agents, but these methods are demanding, have poor safety, and extremely low yields. If phase transfer catalysts (such as quaternary ammonium salts, crown ethers, and polyethylene glycol) are used, mixed bases (such as KOH and K₂CO₃) can replace strong bases, resulting in milder reaction conditions, higher safety, and improved yields. However, phase transfer catalysts are strong surfactants, which complicate the separation and purification of the product. Using modified phase transfer catalysts (such as synergistic effects of phase transfer catalysts and fluoride-supported catalysts, or resin-supported polyethylene glycol), catalyst efficiency can be enhanced and yields increased; however, these catalysts are expensive, increasing production costs.

[0004] In addition, scholars have attempted to use solid bases as catalysts for the N-alkylation of amides. Zhang Chuanxin et al. (Journal of Shangqiu Normal University, 2001, 17, 73-76) used KF / Al₂O₃ + NaOH + K₂CO₃ as the solid base and benzene as the solvent to catalyze the N-alkylation of caprolactam under TBHPAS (tetrabutylammonium 2-hydroxypropyl sulfate) catalysis, achieving a yield of over 92%. However, the reaction still uses strong bases, the operating conditions are harsh, and it is extremely easy to cause environmental pollution. Therefore, it is necessary to find a green method for the N-alkylation of caprolactam. Summary of the Invention

[0005] The purpose of this disclosure is to provide a method for amide alkylation, which employs a non-toxic solvent heterogeneous catalytic system with a catalyst exhibiting high catalytic activity and good chemical stability, enabling efficient catalysis of amide alkylation reactions.

[0006] To achieve the above objectives, this disclosure provides a method for amide alkylation, comprising the following steps:

[0007] Amide compounds and hydrocarbon alcohols are contacted with a catalyst to carry out an amidohydrylation reaction;

[0008] The catalyst mentioned above includes a hierarchical porous titanium-silicon molecular sieve; the hierarchical porous titanium-silicon molecular sieve has multiple cavity structures within its crystals.

[0009] Optionally, the amide compound is selected from one or more of amide compounds, imide compounds, and lactam compounds;

[0010] Preferably, the amide compound is selected from one or more of formamide, acetamide, propionamide, butyramide, valerate, hexamethylenetetramine, heptaamide, octamide, decamide, oleamide, nicotinamide, and benzamide;

[0011] The imide compound is selected from one or more of succinimide, glutarimide, maleimide, dibenzenesulfonamide, and phthalimide;

[0012] The lactam compound is selected from one or more of butyrolactam, valproic acid lactam, caprolactam, heptalactam, octyllactam, and lauryl lactam;

[0013] Optionally, the hydrocarbon group in the hydrocarbon alcohol has 1 to 8 carbon atoms; preferably, the hydrocarbon alcohol is selected from one or more of methanol, ethanol, propanol, butanol and hexanol.

[0014] Optionally, the conditions for the amide alkylation reaction include: a reaction temperature of 200–450°C, preferably 350–400°C; a reaction time of 1–72 h, preferably 10–24 h; a reaction pressure of 0.1–3 MPa, preferably 0.1–2 MPa; and a weight hourly space velocity (WHSV) of 0.2–15 h⁻¹ for the amide compound. -1 Preferably 0.3 to 12 hours -1 The molar ratio of the amide compound to the hydrocarbon alcohol is 1:(3-100), preferably 1:(10-50);

[0015] Optionally, the reactor for the hydrocarbonation reaction is selected from any one of a fixed-bed reactor, a batch reactor, a moving-bed reactor, a suspended-bed reactor, or a slurry-bed reactor.

[0016] Optionally, the size of a single cavity structure of the hierarchical porous titanium-silicon molecular sieve is 2–50 nm, preferably 5–40 nm;

[0017] Preferably, the volume of all the cavity structures accounts for 10-50% of the total volume of the molecular sieve, more preferably 15-45%;

[0018] Optionally, the shape of the cavity structure is selected from one or more of the following: sphere, cube, ellipsoid, and irregular cube.

[0019] Optionally, the hierarchical porous titanium-silicon molecular sieve has the following characteristics: 31 P MAS NMR characteristics:

[0020] The peak intensity of the characteristic peak at a chemical shift of -6±1ppm of the hierarchical porous titanium-silicon molecular sieve is denoted as N1; the peak intensity of the characteristic peak at a chemical shift of -34±1ppm of the hierarchical porous titanium-silicon molecular sieve is denoted as N2; and the peak intensity of the characteristic peak at a chemical shift of -61±1ppm of the hierarchical porous titanium-silicon molecular sieve is denoted as N3.

[0021] X is defined as follows (1-1) 1-1 It can be any value between 0.15 and 0.30;

[0022] X 1-1 = N1 / N3 (1-1); and

[0023] X is defined as follows (1-2) 1-2 It can be any value between 0.10 and 0.25;

[0024] X 1-2 = N2 / N3 (1-2);

[0025] Preferably, the X 1-1 X is any value between 0.18 and 0.29; 1-2 It can be any value between 0.12 and 0.20.

[0026] Optionally, the hierarchical porous titanium-silicon molecular sieve has the following characteristics: 29 Si MAS NMR characteristics:

[0027] The peak area of ​​the spectral peak at the position with a chemical shift of -103±1ppm for the framework heteroatom molecular sieve is denoted as Q. 3 The peak area of ​​the spectral peak at the position with a chemical shift of -113±1ppm for the framework heteroatom molecular sieve is denoted as Q. 4-1 The peak area of ​​the spectral peak at the position with a chemical shift of -116±1ppm for the framework heteroatom molecular sieve is denoted as Q. 4-2 ;

[0028] X is defined as follows (2-1) 2-1 Any value between 0.04 and 0.45:

[0029] X 2-1 =Q 3 / Q 4-1 Equation (2-1);

[0030] X is defined as follows (2-2) 2-2Any value between 0.15 and 0.65:

[0031] X 2-2 =Q 3 / Q 4-2 Equation (2-2);

[0032] Preferably, X 2-1 X is any value between 0.08 and 0.28. 2-2 It can be any value between 0.25 and 0.48.

[0033] Optionally, the hierarchical porous titanium-silicon molecular sieve has the following characteristics: 1 HMAS NMR characteristics:

[0034] The peak area at the chemical shift position of 1.8±0.1ppm is denoted as A1, the peak area at the chemical shift position of 2.2±0.1ppm is denoted as A2, the peak area at the chemical shift position of 2.8±0.1ppm is denoted as A3, the peak area at the chemical shift position of 3.8±0.1ppm is denoted as A4, and the peak area at the chemical shift position of 4.6±0.1ppm is denoted as A5.

[0035] As defined in equation (3), X3 is any value between 0.1 and 1.2:

[0036] X3=A1 / (A2+A3+A4+A5) Formula (3);

[0037] Preferably, X3 is any value between 0.2 and 0.9.

[0038] Optionally, the molar ratio of silicon atoms to titanium atoms in the hierarchical porous titanium-silicon molecular sieve is (10-100):1, preferably (15-80):1;

[0039] Optionally, the multi-level porous titanium silicate molecular sieve is selected from one or more of the following: MFI structured molecular sieve, MEL structured molecular sieve, BEA structured molecular sieve, MWW structured molecular sieve, two-dimensional hexagonal structured molecular sieve, MOR structured molecular sieve, and TUN structured molecular sieve; preferably, it is selected from one or more of the following: MFI structured molecular sieve, MEL structured molecular sieve, BEA structured molecular sieve, MCM structured molecular sieve, and SBA structured molecular sieve; more preferably, it is selected from one or more of the following: MFI structured molecular sieve, MEL structured molecular sieve, and BEA structured molecular sieve.

[0040] Optionally, the multi-level porous titanium silica molecular sieve includes molecular sieve particles composed of a single crystal grain, and / or molecular sieve particles composed of multiple crystal grains aggregated together.

[0041] Optionally, the average particle size of the molecular sieve particles is 0.1–0.8 μm, preferably 0.15–0.65 μm; the BET specific surface area is 250–650 m². 2 / g, preferably 280-600m 2 / g; microporous specific surface area is 280-550m² 2 / g, preferably 300-500m 2 / g; total pore volume is 0.2–0.55 cm³. 3 / g, preferably 0.25~0.50cm 3 / g; mesopore volume is 0.1–0.4 cm³. 3 / g, preferably 0.15~0.35cm 3 / g;

[0042] Optionally, a hysteresis loop exists between the adsorption isotherm and desorption isotherm of the low-temperature nitrogen adsorption of the multi-level porous titanium-silicon molecular sieve; preferably, the initial relative pressure (P / P0) at which the hysteresis loop appears is 0.3 to 0.55.

[0043] Optionally, the hierarchical porous titanium-silicon molecular sieve is prepared by a method comprising the following steps:

[0044] S1. Mix the titanium source, silicon source, first template agent, water, silanizing agent and structural filler to obtain a reaction mixture;

[0045] S2. The reaction mixture is subjected to a first hydrothermal crystallization treatment and a first calcination treatment in sequence to obtain a molecular sieve intermediate;

[0046] S3. Mix the molecular sieve intermediate, the second template agent and water, and then perform a second hydrothermal crystallization treatment and a second calcination treatment in sequence.

[0047] Optionally, in step S1, the molar ratio of titanium source: silicon source: first template agent: water: silanizing agent is (0.002~0.15):1:(0.01~4):(1~50):(0.02~0.35); preferably (0.01~0.06):1:(0.02~1.5):(10~30):(0.03~0.15); the weight ratio of SiO2 to structural filler in the reaction mixture is (5~50):1, preferably (8~30):1.

[0048] Optionally, in step S1, the silicon source is selected from at least one of silicone grease, solid silica gel, fumed silica, and silica sol; preferably, it is selected from at least one of silicone grease, solid silica gel, and fumed silica.

[0049] A further preferred option is a silicone grease, wherein the silicone grease has the general formula shown in formula (A):

[0050]

[0051] Where R a R b R c R d Each is independently selected from alkyl groups having 1 to 6 carbon atoms, wherein the alkyl group is branched or straight-chain alkyl; preferably, R a R b R c R d Each is independently selected from straight-chain alkyl groups having 1 to 4 carbon atoms or branched alkyl groups having 3 to 4 carbon atoms; more preferably, the R a R b R c R d Each of the following is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, or tert-butyl; more preferably, the silicone grease is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate, and dimethyl diethyl silicone grease.

[0052] Optionally, the first template agent in step S1 and the second template agent in step S3 are organic bases; and each is preferably selected independently from at least one of quaternary ammonium bases, aliphatic amines and aliphatic alcohol amines;

[0053] More preferably, the first template agent and the second template agent are each independently selected from at least one of quaternary ammonium bases having the structure shown in formula (B):

[0054] R1, R2, R3 and R4 are each selected from alkyl groups having 1 to 4 carbon atoms, preferably one or more of straight-chain alkyl groups having 1 to 4 carbon atoms and branched alkyl groups having 3 to 4 carbon atoms, and more preferably, R1, R2, R3 and R4 are each selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl.

[0055] More preferably, the first template agent and the second template agent are each independently tetrapropylammonium hydroxide or a mixture of tetrapropylammonium hydroxide and one or more selected from tetrapropylammonium chloride and tetrapropylammonium bromide.

[0056] Optionally, in step S1, the titanium source is selected from one or more of organic titanium sources and inorganic titanium sources;

[0057] The organic titanium source is a titanium-containing organic ester, selected from at least one of the structures represented by the general formula (C) below:

[0058]

[0059] R5, R6, R7, and R8 are each selected from alkyl groups having 1 to 6 carbon atoms, preferably straight-chain alkyl groups having 1 to 4 carbon atoms and branched alkyl groups having 3 to 6 carbon atoms, and more preferably straight-chain alkyl groups having 2 to 4 carbon atoms and branched alkyl groups having 2 to 4 carbon atoms; optionally, R5, R6, R7, and R8 are each selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl, or isohexyl; preferably, each is independently selected from ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, or tert-butyl.

[0060] The inorganic titanium source is selected from one or more of titanium chloride, nitrate or sulfate;

[0061] Preferably, the titanium source is selected from one or more of titanium tetrachloride, titanium sulfate, titanium nitrate, tetraethyl titanate, tetrapropyl titanate, and tetrabutyl titanate.

[0062] Optionally, in step S1, the silanizing agent has the general formula R9Si(R 10 (R) 11 )R 12 Among them, R9 and R 10 R 11 R 12 Each can be independently a halogen, alkyl, alkoxy, aromatic, mercapto, or amino group, and R9, R 10 R 11 R 12 At least one of them is an alkyl, alkoxy, aromatic, mercapto, or amino group; the alkyl, alkoxy, mercapto, and amino groups each have an independent number of carbon atoms of C1 to C2. 18 ;

[0063] Preferably, the silanizing agent is selected from one or more of dimethyldichlorosilane, N-phenyl-3-aminopropyltrimethoxysilane, phenyltrimethoxysilane, 1,7-dichlorooctylmethyltetrasiloxane, hexadecyltrimethoxysilane, octyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane; more preferably, it is selected from one or more of N-phenyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane.

[0064] Optionally, in step S1, the structural filler is selected from one or more of amphiphilic surfactants and hard template agents;

[0065] Preferably, the amphiphilic surfactant is selected from one or more of hexadecyltrimethylammonium bromide, sodium dodecylbenzene sulfonate, branched sodium dodecylbenzene sulfonate, α-olefin sulfonates with 14 to 16 carbon atoms, and secondary alkyl sulfonates.

[0066] Preferably, the hard template agent is selected from one or more of PEO-PPO-PEO block copolymers, mesoporous carbon, natural fibers, polyethylene, polypropylene, polyvinyl chloride, polystyrene, and polyvinyl alcohol;

[0067] More preferably, the structural filler is selected from one or more of hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, PEO-PPO-PEO block copolymer, mesoporous carbon, and natural cellulose.

[0068] Optionally, step S1 includes:

[0069] a. Mix titanium source, silicon source, first template agent and water to obtain silicon hydrolysis sol;

[0070] b. Add the silanizing agent and the structural filler to the hydrolyzed sol of the silicon respectively, and mix them to obtain the reaction mixture;

[0071] Optionally, the mixing conditions in step a include stirring at 40–90°C for 6–12 hours;

[0072] Optionally, the mixing conditions in step b include stirring at 20–50°C for 2–4 hours;

[0073] Preferably, the silicon source is an organosilicon grease, and step a further includes a hydrolysis and alcohol removal treatment after mixing the silicon source, the first template agent and water to obtain the silicon hydrolysate;

[0074] Optionally, the conditions for the hydrolysis and alcohol removal treatment include: stirring and hydrolyzing at 40–90°C for 6–12 hours; preferably, stirring and hydrolyzing at 60–85°C for 8–10 hours.

[0075] Optionally, in step S3, the weight ratio of the second template agent: water: molecular sieve intermediate is (0.2-3.5):(2-50):1; preferably (0.25-2.2):(3-35):1.

[0076] Optionally, the conditions for the first hydrothermal crystallization treatment in step S2 and the second hydrothermal crystallization treatment in step S3 each independently include: a hydrothermal crystallization time of 6–168 h and a hydrothermal crystallization temperature of 130–200 °C; preferably, a hydrothermal crystallization time of 24–72 h and a hydrothermal crystallization temperature of 150–180 °C; and the pressure is self-generated pressure.

[0077] The conditions for the first roasting treatment in step S2 and the second roasting treatment in step S3 each independently include: a roasting temperature of 300-700℃ and a roasting time of 1-16h; preferably, a roasting temperature of 400-600℃ and a roasting time of 2-5h.

[0078] Through the above technical solution, this disclosure provides a method for amide hydrocarbonation, which enables amide hydrocarbonation reactions in heterogeneous, non-toxic solvent systems. The reaction process does not require the use of toxic or harmful solvents, and high amide conversion and selectivity can be obtained under mild reaction conditions, making it highly valuable for industrial applications. The catalyst used includes a hierarchical porous titanium-silicon molecular sieve, incorporating titanium atom active centers to enhance its resistance to deactivation. Furthermore, the molecular sieve has a multi-cavity structure within its crystals, containing abundant silanol active centers. This multi-cavity structure provides numerous independent reaction units, and the concentrated distribution of silanol active centers allows the molecular sieve to simultaneously possess… It possesses both acid and Lewis acid properties, along with a large specific surface area and pore volume, which is beneficial for efficient catalytic reactions.

[0079] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description

[0080] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings:

[0081] Figure 1 TEM electron microscope image of the molecular sieve product obtained in Example 1;

[0082] Figure 2 The XRD pattern of the molecular sieve product obtained in Example 1 was prepared.

[0083] Figure 3 To prepare the molecular sieve product obtained in Example 1 31 P-TMP MAS NMR spectrum;

[0084] Figure 4 The IR-OH spectrum of the molecular sieve product obtained in Example 1 was prepared.

[0085] Figure 5 To prepare the molecular sieve product obtained in Example 1 29 Si MAS NMR spectrum;

[0086] Figure 6 To prepare the molecular sieve product obtained in Example 1 1 HMAS NMR spectrum;

[0087] Figure 7 SEM images of the molecular sieve products obtained in Example 1;

[0088] Figure 8 The BET curve of the molecular sieve product obtained in Example 1 is shown.

[0089] Figure 9 TEM electron microscope image of the intermediate product obtained in Example 1;

[0090] Figure 10 The XRD pattern of the molecular sieve product obtained in Example 10 is shown.

[0091] Figure 11 The XRD pattern of the molecular sieve product obtained in Example 11. Detailed Implementation

[0092] The following provides a detailed description of specific embodiments of this disclosure. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of this disclosure.

[0093] This disclosure provides a method for amide alkylation, comprising the following steps:

[0094] Amide compounds and hydrocarbon alcohols are contacted with a catalyst to carry out an amidohydrylation reaction;

[0095] The catalyst mentioned above includes a hierarchical porous titanium-silicon molecular sieve; the hierarchical porous titanium-silicon molecular sieve has multiple cavity structures within its crystals.

[0096] This disclosure provides a method for amide hydrocarbonation, enabling the amide hydrocarbonation reaction in a heterogeneous, non-toxic solvent system. The reaction process does not require the use of toxic or harmful solvents, and high amide conversion and selectivity can be obtained under mild reaction conditions, making it highly valuable for industrial applications. The catalyst used comprises a hierarchical porous titanium-silicon molecular sieve, incorporating titanium atoms as active centers to enhance its resistance to deactivation. Furthermore, the molecular sieve possesses a multi-cavity structure with abundant silanol active centers, providing numerous independent reaction units. The concentrated distribution of silanol active centers allows the molecular sieve to simultaneously possess… It possesses both acid and Lewis acid properties, along with a large specific surface area and pore volume, which is beneficial for efficient catalytic reactions.

[0097] In one embodiment, the amide compound is selected from one or more of amide compounds, imide compounds, and lactam compounds. The amide alkylation method provided in this disclosure is widely applicable to a variety of amide compounds.

[0098] In one specific embodiment, the amide compound is selected from one or more of formamide, acetamide, propionamide, butyramide, pentamide, hexamide, heptaamide, octamide, decamide, oleamide, nicotinamide, and benzamide;

[0099] The imide compound is selected from one or more of succinimide, glutarimide, maleimide, dibenzenesulfonamide, and phthalimide;

[0100] The lactam compound is selected from one or more of butyrolactam, valproic acid lactam, caprolactam, heptalactam, octyllactam, and lauryl lactam.

[0101] In one embodiment, the hydrocarbon group in the hydrocarbon alcohol has 1 to 8 carbon atoms; preferably, the hydrocarbon alcohol is selected from one or more of methanol, ethanol, propanol, butanol and hexanol.

[0102] In one embodiment, the conditions for the amide alkylation reaction include: a reaction temperature of 200–450°C; a reaction time of 1–72 h; a reaction pressure of 0.1–3 MPa; and a weight hourly space velocity (WHSV) of 0.2–15 h⁻¹ for the amide compound. -1 The molar ratio of the amide compound to the hydrocarbon alcohol is 1:(3-100).

[0103] In a preferred embodiment, the conditions for the amide alkylation reaction include: a reaction temperature of 350–400°C; a reaction time of 10–24 h; a reaction pressure of 0.1–2 MPa; and a weight hourly space velocity (WHSV) of 0.3–12 h⁻¹ for the amide compound. -1 The molar ratio of the amide compound to the alkyl alcohol is 1:(10-50). Following this embodiment, the amide alkylation reaction is beneficial for improving the conversion rate of the amide compound and the selectivity of the N-alkylated amide.

[0104] In one specific embodiment, the reactor for the hydrocarbonation reaction is selected from any one of a fixed-bed reactor, a batch reactor, a moving-bed reactor, a suspended-bed reactor, or a slurry-bed reactor.

[0105] The hierarchical porous titanium-silicon molecular sieve used in the amide hydrocarbonation reaction has multiple large-sized cavities within the crystal, which facilitates the catalytic reaction.

[0106] In one specific embodiment, the size of a single cavity structure in the hierarchical porous titanium-silicon molecular sieve is 2–50 nm, preferably 5–40 nm. Optionally, the shape of the cavity structure is selected from one or more of the following: spherical, cubic, ellipsoidal, and irregular cube.

[0107] In a preferred embodiment, the volume of all the cavity structures accounts for 10-50% of the total volume of the molecular sieve, more preferably 15-45%.

[0108] In a preferred embodiment, the hierarchical porous titanium-silicon molecular sieve has the following characteristics: 31 P MAS NMR characteristics:

[0109] The peak intensity of the characteristic peak at a chemical shift of -6±1ppm of the hierarchical porous titanium-silicon molecular sieve is denoted as N1; the peak intensity of the characteristic peak at a chemical shift of -34±1ppm of the hierarchical porous titanium-silicon molecular sieve is denoted as N2; and the peak intensity of the characteristic peak at a chemical shift of -61±1ppm of the hierarchical porous titanium-silicon molecular sieve is denoted as N3.

[0110] X is defined as follows (1-1) 1-1 It can be any value between 0.15 and 0.30;

[0111] X 1-1 = N1 / N3 (1-1); and

[0112] X is defined as follows (1-2) 1-2 It can be any value between 0.10 and 0.25;

[0113] X 1-2 = N2 / N3 (1-2);

[0114] Preferably, the X 1-1 X is any value between 0.18 and 0.29; 1-2 It can be any value between 0.12 and 0.20.

[0115] The inventors of this disclosure have discovered that when a multi-level porous titanium-silicon molecular sieve simultaneously possesses... When considering acid and Lewis acid properties, trimethylphosphorus (TMP) is used as a probe molecule. 31 In the pMAS NMR spectrum, the peak with a chemical shift of -6 ± 1 ppm was used as... The characteristic peaks of the acid properties were determined, with the peak at a chemical shift of -34±1 ppm taken as the characteristic peak of Lewis acid properties, and the peak at a chemical shift of -61±1 ppm taken as the characteristic peak of TMP physisorption. Using this characteristic peak of TMP physisorption as a benchmark, [the following was determined]. The characteristic peaks of the acid properties and the Lewis acid properties were compared with the characteristic peak of the TMP physisorption. The ratio of the peak intensity of each of the two acid properties to the peak intensity of the TMP physisorption characteristic peak was satisfied with the above X. 1-1 and X 1-2When the range is within the specified range, the hierarchical porous titanium silicate molecular sieve can exhibit higher N-alkylation amide selectivity and catalyst stability in amide alkylation reactions.

[0116] In this disclosure, for hierarchical porous titanium-silicon molecular sieves... 31 Trimethylphosphorus (TMP) was used as the probe molecule in the P-TMP MAS NMR spectrum test, and the test method was a conventional method in this field.

[0117] In a preferred embodiment, the hierarchical porous titanium-silicon molecular sieve has the following characteristics: 29 Si MAS NMR characteristics:

[0118] The peak area of ​​the spectral peak at the position with a chemical shift of -103±1ppm for the framework heteroatom molecular sieve is denoted as Q. 3 The peak area of ​​the spectral peak at the position with a chemical shift of -113±1ppm for the framework heteroatom molecular sieve is denoted as Q. 4-1 The peak area of ​​the spectral peak at the position with a chemical shift of -116±1ppm for the framework heteroatom molecular sieve is denoted as Q. 4-2 ;

[0119] X is defined as follows (2-1) 2-1 Any value between 0.04 and 0.45:

[0120] X 2-1 =Q 3 / Q 4-1 Equation (2-1);

[0121] X is defined as follows (2-2) 2-2 Any value between 0.15 and 0.65:

[0122] X 2-2 =Q 3 / Q 4-2 Equation (2-2);

[0123] Preferably, X 2-1 X is any value between 0.08 and 0.28. 2-2 The value can be any value between 0.25 and 0.48. The titanium-silicon molecular sieve used in this embodiment has abundant silanol active centers, which can achieve higher selectivity for N-alkylated amides in the amide alkylation reaction.

[0124] In a preferred embodiment, the hierarchical porous titanium-silicon molecular sieve has the following characteristics: 1 HMAS NMR characteristics:

[0125] The peak area at the chemical shift position of 1.8±0.1ppm is denoted as A1, the peak area at the chemical shift position of 2.2±0.1ppm is denoted as A2, the peak area at the chemical shift position of 2.8±0.1ppm is denoted as A3, the peak area at the chemical shift position of 3.8±0.1ppm is denoted as A4, and the peak area at the chemical shift position of 4.6±0.1ppm is denoted as A5.

[0126] As defined in equation (3), X3 is any value between 0.1 and 1.2:

[0127] X3=A1 / (A2+A3+A4+A5) Formula (3);

[0128] Preferably, X3 is any value between 0.2 and 0.9. In this disclosure, the multi-level porous titanium-silicon molecular sieve... 1 In the HMAS NMR spectrum, the peak at a chemical shift of 1.8 ± 0.1 ppm represents isolated silanol groups in the molecular sieve, while the peaks with chemical shifts in the range of 2–6 ppm (2.8 ppm ± 0.1 ppm, 3.8 ± 0.1 ppm, and 4.6 ± 0.1 ppm) represent silanol groups with hydrogen bonding interactions. The titanium-silicon molecular sieve contains a small amount of isolated silanol groups and a large number of silanol groups with hydrogen bonding interactions, which helps to improve the selectivity of N-alkylated amides in amide alkylation reactions.

[0129] In one embodiment, the molar ratio of silicon atoms to titanium atoms in the hierarchical porous titanium-silicon molecular sieve is (10-100):1, preferably (15-80):1; the present disclosure obtains the molar ratio of silicon atoms to titanium atoms in the molecular sieve by X-ray fluorescence spectrometry analysis.

[0130] In one specific embodiment, the multi-level porous titanium silicate molecular sieve is selected from one or more of the following: MFI structured molecular sieve, MEL structured molecular sieve, BEA structured molecular sieve, MWW structured molecular sieve, two-dimensional hexagonal structured molecular sieve, MOR structured molecular sieve, and TUN structured molecular sieve; preferably selected from one or more of the following: MFI structured molecular sieve, MEL structured molecular sieve, BEA structured molecular sieve, MCM structured molecular sieve, and SBA structured molecular sieve; more preferably selected from one or more of the following: MFI structured molecular sieve, MEL structured molecular sieve, and BEA structured molecular sieve.

[0131] In one specific embodiment, the multi-level porous titanium-silicon molecular sieve includes molecular sieve particles composed of a single crystal grain, and / or molecular sieve particles composed of multiple crystal grains aggregated together.

[0132] Optionally, the average particle size of the molecular sieve particles is 0.1–0.8 μm, preferably 0.15–0.65 μm; the BET specific surface area is 250–650 m².2 / g, preferably 280-600m 2 / g; microporous specific surface area is 280-550m² 2 / g, preferably 300-500m 2 / g; total pore volume is 0.2–0.55 cm³. 3 / g, preferably 0.25~0.50cm 3 / g; mesopore volume is 0.1–0.4 cm³. 3 / g, preferably 0.15~0.35cm 3 / g.

[0133] In one embodiment, a hysteresis loop exists between the adsorption isotherm and desorption isotherm of the low-temperature nitrogen adsorption of the multi-level porous titanium-silicon molecular sieve; preferably, the initial relative pressure (P / P0) at which the hysteresis loop appears is 0.3 to 0.55.

[0134] In a preferred embodiment, the hierarchical porous titanium-silicon molecular sieve is prepared by a method comprising the following steps:

[0135] S1. Mix the titanium source, silicon source, first template agent, water, silanizing agent and structural filler to obtain a reaction mixture;

[0136] S2. The reaction mixture is subjected to a first hydrothermal crystallization treatment and a first calcination treatment in sequence to obtain a molecular sieve intermediate;

[0137] S3. Mix the molecular sieve intermediate, the second template agent and water, and then perform a second hydrothermal crystallization treatment and a second calcination treatment in sequence.

[0138] According to this embodiment, a hierarchical porous titanium-silicon molecular sieve is prepared by introducing a titanium source into the reaction raw materials, which can introduce active titanium atom centers into the molecular sieve framework during the molecular sieve synthesis process. By introducing silanizing reagents and macromolecular structural fillers into the molecular sieve synthesis raw materials, the effect of molecular sieve layer expansion and pore expansion can be generated, and a molecular sieve material with open channels can be prepared. Then, a second template agent is added for dissolution and recrystallization to prepare a hierarchical porous titanium-silicon molecular sieve with a multi-cavity structure.

[0139] Specifically, during the preparation of molecular sieves, the silanizing reagent's silanol groups can hydrolyze and condense with the silanol groups of the organosilicon source to generate stable Si-O-Si bonds, thus ensuring the achievement of the pore-expanding effect. Furthermore, the long carbon chain of the silanizing reagent and the structural filler of the amphiphilic surfactant can form stable and controllable structural units (the long carbon chain of the silanizing reagent and the hydrophobic group of the surfactant are close to each other and interact by van der Waals forces), thereby playing a fine-tuning role in pore expansion; or, a size-controllable hard template agent can be used to fill the space, enabling the molecular sieve to produce an ordered, mesoporous structure with controllable pore size (controlled by the chain length of the alkyl chain of the silanizing reagent); then, a second template agent is introduced into the molecular sieve with open pores, utilizing its dissolution-recrystallization mechanism to obtain a multi-level porous titanium-silicon molecular sieve.

[0140] In one embodiment, in step S1, the molar ratio of titanium source: silicon source: first template agent: water: silanizing agent is (0.002~0.15):1:(0.01~4):(1~50):(0.02~0.35); the weight ratio of SiO2 to structural filler in the reaction mixture is (5~50):1.

[0141] In a preferred embodiment, in step S1, the molar ratio of titanium source: silicon source: first template agent: water: silanizing agent is (0.01-0.06):1:(0.02-1.5):(10-30):(0.03-0.15); the weight ratio of SiO2 to structural filler in the reaction mixture is (8-30):1. The titanium-silicon molecular sieve prepared according to this embodiment has higher catalytic activity and reaction stability.

[0142] In one embodiment, in step S1, the silicon source is selected from at least one of silicone grease, solid silicone, fumed silica, and silica sol; preferably, it is selected from at least one of silicone grease, solid silicone, and fumed silica.

[0143] A further preferred option is a silicone grease, wherein the silicone grease has the general formula shown in formula (A):

[0144]

[0145] Where R a R b R c R d Each is independently selected from alkyl groups having 1 to 6 carbon atoms, wherein the alkyl group is branched or straight-chain alkyl; preferably, R a R b R c R dEach is independently selected from straight-chain alkyl groups having 1 to 4 carbon atoms or branched alkyl groups having 3 to 4 carbon atoms; more preferably, the R a R b R c R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, or tert-butyl.

[0146] In a preferred embodiment, the silicone grease is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate, and dimethyl diethyl silicone grease.

[0147] In one embodiment, in step S1, the first template agent is an organic base, preferably at least one selected from quaternary ammonium bases, aliphatic amines, and aliphatic alcohol amines.

[0148] In one specific embodiment, the first template agent is selected from at least one of quaternary ammonium bases having the structure shown in formula (B):

[0149] R1, R2, R3 and R4 are each selected from alkyl groups having 1 to 4 carbon atoms, preferably one or more of straight-chain alkyl groups having 1 to 4 carbon atoms and branched alkyl groups having 3 to 4 carbon atoms, and more preferably, R1, R2, R3 and R4 are each selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl.

[0150] In a preferred embodiment, the first template agent is tetrapropylammonium hydroxide or a mixture of tetrapropylammonium hydroxide and one or more selected from tetrapropylammonium chloride and tetrapropylammonium bromide.

[0151] In one embodiment, step S1 includes:

[0152] a. Mix titanium source, silicon source, first template agent and water to obtain silicon hydrolysis sol;

[0153] b. Add the silanizing agent and the structural filler to the hydrolyzed sol of the silicon respectively, and mix them to obtain the reaction mixture;

[0154] Optionally, the mixing conditions in step a include stirring at 40–90°C for 6–12 hours;

[0155] Optionally, the mixing conditions in step b include stirring at 20–50°C for 2–4 hours.

[0156] In one specific embodiment, the silicon source is an organosilicon grease, and step a further includes a hydrolysis and alcohol removal treatment after mixing the silicon source, the first template agent and water to obtain the silicon hydrolysate;

[0157] Optionally, the conditions for the hydrolysis-induced alcohol removal treatment include: stirring and hydrolyzing at 40–90°C for 6–12 hours; preferably, stirring and hydrolyzing at 60–85°C for 8–10 hours. Preferably, the hydrolysis-induced alcohol removal treatment results in the alcohol content in the silicone hydrolysate of the obtained silicone grease being below 10 ppm by mass.

[0158] In one embodiment, in step S1, the titanium source is selected from one or more of organic titanium sources and inorganic titanium sources;

[0159] The organic titanium source is a titanium-containing organic ester, selected from at least one of the structures represented by the general formula (C) below:

[0160]

[0161] R5, R6, R7, and R8 are each selected from alkyl groups having 1 to 6 carbon atoms, preferably straight-chain alkyl groups having 1 to 4 carbon atoms and branched alkyl groups having 3 to 6 carbon atoms, and more preferably straight-chain alkyl groups having 2 to 4 carbon atoms and branched alkyl groups having 2 to 4 carbon atoms; optionally, R5, R6, R7, and R8 are each selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl, or isohexyl; preferably, each is independently selected from ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, or tert-butyl.

[0162] The inorganic titanium source is selected from one or more of titanium chloride, nitrate or sulfate.

[0163] In a preferred embodiment, the titanium source is selected from one or more of titanium tetrachloride, titanium sulfate, titanium nitrate, tetraethyl titanate, tetrapropyl titanate, and tetrabutyl titanate.

[0164] In one embodiment, in step S1, the silanizing agent has the general formula R9Si(R 10 (R) 11 )R 12 Among them, R9 and R 10 R 11 R 12 Each can be independently a halogen, alkyl, alkoxy, aromatic, mercapto, or amino group, and R9, R 10 R 11 R 12At least one of them is an alkyl, alkoxy, aromatic, mercapto, or amino group; the alkyl, alkoxy, mercapto, and amino groups each have an independent number of carbon atoms of C1 to C2. 18 .

[0165] In one specific embodiment, the silanizing agent is selected from one or more of dimethyldichlorosilane, N-phenyl-3-aminopropyltrimethoxysilane, phenyltrimethoxysilane, 1,7-dichlorooctylmethyltetrasiloxane, hexadecyltrimethoxysilane, octyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane; more preferably, it is selected from one or more of N-phenyl-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane.

[0166] In one embodiment, the structural filler is selected from one or more of amphiphilic surfactants and hard template agents.

[0167] In one specific embodiment, the amphiphilic surfactant is selected from one or more of hexadecyltrimethylammonium bromide, sodium dodecylbenzene sulfonate, branched sodium dodecylbenzene sulfonate, α-olefin sulfonates with 14 to 16 carbon atoms, and secondary alkyl sulfonates.

[0168] The hard template agent is selected from one or more of PEO-PPO-PEO block copolymers, mesoporous carbon, natural fibers, polyethylene, polypropylene, polyvinyl chloride, polystyrene, and polyvinyl alcohol.

[0169] In a preferred embodiment, the structural filler is selected from one or more of hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, PEO-PPO-PEO block copolymer, mesoporous carbon, and natural cellulose.

[0170] All reagents used in this disclosure can be purchased through conventional channels or prepared using known methods.

[0171] In one embodiment, the conditions for the first hydrothermal crystallization treatment in step S2 include: hydrothermal crystallization time of 6 to 168 hours, hydrothermal crystallization temperature of 130 to 200°C, and pressure of autogenous pressure;

[0172] The conditions for the first calcination treatment in step S2 include: a calcination temperature of 300–700°C and a calcination time of 1–16 h.

[0173] In a preferred embodiment, the conditions for the first hydrothermal crystallization treatment in step S2 include: a hydrothermal crystallization time of 24–72 h, a hydrothermal crystallization temperature of 150–180 °C, and an autogenous pressure.

[0174] The conditions for the first calcination treatment in step S2 include: a calcination temperature of 400–600°C and a calcination time of 2–5 hours. The hierarchical porous titanium-silicon molecular sieve prepared according to this embodiment exhibits better catalytic activity.

[0175] In one specific embodiment, after the first hydrothermal crystallization treatment, the method further includes the steps of subjecting the product of the first hydrothermal crystallization treatment to a first filtration treatment and a first drying treatment, followed by the first calcination treatment. The temperature of the first drying treatment is 50–120°C, and the time is 1–12 hours.

[0176] In one embodiment, in step S3, the selection range of the second template agent is the same as that of the first template agent, which will not be repeated here; preferably, the first template agent and the second template agent are the same template agent.

[0177] In one embodiment, in step S3, the weight ratio of the second template agent: water: molecular sieve intermediate is (0.2-3.5):(2-50):1; preferably (0.25-2.2):(3-35):1. By preparing the sieve according to the preferred weight ratio in this embodiment, a molecular sieve with higher catalytic activity can be obtained.

[0178] In one embodiment, the conditions for the second hydrothermal crystallization treatment in step S3 include: a hydrothermal crystallization time of 6–168 h, a hydrothermal crystallization temperature of 130–200 °C, and an autogenous pressure;

[0179] The conditions for the second calcination treatment in step S3 include: a calcination temperature of 300–700°C and a calcination time of 1–16 h.

[0180] In a preferred embodiment, the conditions for the second hydrothermal crystallization treatment in step S3 include: a hydrothermal crystallization time of 24–72 h, a hydrothermal crystallization temperature of 150–180 °C, and an autogenous pressure.

[0181] The conditions for the second calcination treatment in step S3 include: a calcination temperature of 400–600°C and a calcination time of 2–5 hours.

[0182] In one specific embodiment, after the second hydrothermal crystallization treatment, the method further includes a second filtration treatment and a second drying treatment of the product from the second hydrothermal crystallization treatment, followed by the second calcination treatment. The temperature of the second drying treatment is 50–120°C, and the time is 1–12 hours.

[0183] The present disclosure will be described in detail below through embodiments. However, the present disclosure is not limited to the contents of the following embodiments.

[0184] The sample 31 P-TMP MAS NMR characterization was performed using an AVANCEⅢ 600WB nuclear magnetic resonance spectrometer with a 4mm dual resonance probe, a Ф4mm ZrO2 rotor, a resonance frequency of 242.9MHz, a magic angle rotation speed of 10kHz, a pulse width of 1.4μs, a cycle delay of 1s, and approximately 6000 scans.

[0185] Q of the sample 3 / Q 4 Measurement method adopted 29 The Si MAS NMR method was used on an AVANCEⅢ500WB nuclear magnetic resonance spectrometer with a 7mm dual resonance probe, a Ф7mm ZrO2 rotor, a resonance frequency of 99.3MHz, a magic angle rotation speed of 5kHz, a pulse width of 1.8μs, a cycle delay time of 2s, and approximately 3000 scans.

[0186] The sample 1 H MAS NMR spectra were obtained on a Varian Infinityplus-400 spectrometer using a 4mm dual resonance probe, a Ф4mm ZrO2 rotor, a resonance frequency of 400.1MHz, a magic angle rotation speed of 10kHz, a pulse width of 3.57μs, a cycle delay of 1s, and approximately 4000 scans.

[0187] The infrared hydroxyl spectrum (IR-OH) of the samples was measured on a Nicolet 8210 Fourier transform infrared spectrometer, with a measurement range of 400–4000 cm⁻¹. -1 .

[0188] The X-ray diffraction (XRD) phase pattern of the sample was determined on a Siemens D5005 X-ray diffractometer with Kα (Cu) as the X-ray source and the test range 2θ from 0.5° to 70°.

[0189] Transmission electron microscopy (TEM) images of the samples were obtained using a Tecnai G2F20S-TWIN TEM microscope from FEI. The cavity structure and its dimensions were determined based on TEM measurements. The volume fraction of the cavity structure relative to the total volume of the molecular sieve was obtained by measuring the TEM images: the volume of each cavity in the molecular sieve particles was measured based on the TEM images (calculated spherically, using the median of the sum of the maximum and minimum lengths passing through the center of the cavity structure as the spherical diameter, then obtaining the spherical radius, and finally calculating the percentage of the total volume of all cavities relative to the total volume of the molecular sieve particles; the average value was taken after calculating the cavity structure volume fraction of 50 molecular sieve particles).

[0190] Scanning electron microscopy (SEM) images of the samples were obtained using a Hitachi S4800 high-resolution cold field emission scanning electron microscope. The average particle size of the samples was determined by measuring the SEM images (the average value was taken after testing the particle size of 50 molecular sieves).

[0191] The total specific surface area and total pore volume of the samples were determined using a Micromeritics ASAP245 static nitrogen adsorption analyzer according to the ASTM D4222-98 standard method. The adsorption and desorption isotherms of the samples at low temperatures were determined according to the ASTM D4222-98 standard method.

[0192] X-ray fluorescence analysis (determination of the molar ratio of silicon to titanium in molecular sieves) was performed using a Rigaku Electric Co., Ltd. 3013 instrument with a tungsten target, an excitation voltage of 40 kV, and an excitation current of 250 mA.

[0193] The reagents used in the following examples and comparative examples were all purchased through conventional channels.

[0194] The following preparation examples demonstrate the preparation of hierarchical porous titanium-silicon molecular sieves.

[0195] Preparation Example 1

[0196] (1) Add 6g tetrabutyl titanate (0.0176mol), 104g tetraethyl silicate (0.5mol), 65g tetrapropylammonium hydroxide (TPAOH, 0.08mol) aqueous solution with a concentration of 25% by weight and 140g water to a 500mL beaker, place it on a magnetic stirrer with heating and stirring functions and mix evenly. Stir at 60℃ for 5 hours, and replenish the evaporated water at regular intervals to obtain a colorless and transparent titanium silica gel solution.

[0197] (2) Add 9g of N-phenyl-3-aminopropyltrimethoxysilane (PHAPTMS, 0.035mol) and 3g of PEO-PPO-PEO triblock copolymer (P123, purchased from Inokai, weight average molecular weight 5800) to the mixture in step (1) and stir for 2 hours.

[0198] (3) The mixture obtained in step (2) is transferred to a stainless steel sealed reactor and crystallized at 170°C for 24 hours to obtain a sample. The sample is filtered, washed, dried at 110°C for 3 hours, and then calcined in a muffle furnace at 550°C for 3 hours to obtain intermediate product M-1 (molecular sieve intermediate).

[0199] (4) Mix 10g of M-1 molecular sieve intermediate, 20g of 25% by weight tetrapropylammonium hydroxide (TPAOH, 5g) aqueous solution and 40g of water evenly (the weight ratio of second template agent: water: molecular sieve intermediate is 0.5:5.5:1), transfer to a stainless steel closed reactor, and crystallize at 170℃ for 24h to obtain a sample. Filter and wash the obtained sample, dry it at 110℃ for 3 hours, and then calcine it in a muffle furnace at 550℃ for 3 hours to obtain a multi-level porous titanium silicon molecular sieve sample, denoted as CAT-1.

[0200] The structural parameter characterization results of sample CAT-1 are listed in Table 2;

[0201] TEM electron microscope image of sample CAT-1 as follows Figure 1 As shown in the figure, the molecular sieve has a hierarchical porous structure with multiple cavities within the crystal; and the size of a single cavity structure is 5–35 nm; the TEM image of the intermediate product M-1 before dissolution and recrystallization is as follows. Figure 9 As shown, Figure 9 and Figure 1 By comparison, it can be seen that Figure 1 The intermediate products, after being dissolved and recrystallized, created a large number of intracrystalline multi-cavity structures;

[0202] The XRD pattern of sample CAT-1 is as follows Figure 2 As shown, this indicates that the titanium silicate molecular sieve sample has an MFI topology.

[0203] Sample CAT-1 31 p-TMP MAS NMR spectrum as shown Figure 3 As shown in the figure, CAT-1 has a chemical shift of -6 ppm. The acid signal, the Lewis acid signal at a chemical shift of -34 ppm, and the TMP physisorption signal at a chemical shift of -61 ppm, with the intensity values ​​of each peak being: N1 40175, N2 31842, N3 216929, and X calculated using equations (1-1) to (1-2). 1-1 and X 1-2 The values ​​are listed in Table 3;

[0204] The infrared hydroxyl spectrum of sample CAT-1 is as follows: Figure 4 As shown, distinct silanol active centers can be observed, with the 3740 cm⁻¹ site being particularly prominent. -1 The spectral peak at position 3690 cm⁻¹ represents a terminal hydroxyl group, indicating a side reaction center. -1 The spectral peak at position 3500 cm⁻¹ is for the ortho-hydroxyl group; -1 The spectral peak at the position is a nested silanol, indicating the main reaction center;

[0205] Sample CAT-129 Si MAS NMR spectrum as shown Figure 5 As shown in the figure, peaks are observed at chemical shifts of -103 ppm, -113 ppm, and -116 ppm, indicating that the molecular sieve sample contains silicon with silanol active centers and two coordination environments without hydroxyl groups. The peak areas Q of the three peaks were calculated by integration. 3 For 191772, Q 4-1 The value is 1225867, Q 4-2 X is 480975, calculated using equations (2-1) to (2-2). 2-1 and X 2-2 The values ​​are listed in Table 3;

[0206] Sample CAT-1 1 HMAS NMR spectrum as follows Figure 6 As shown in the figure, the titanium-silicon molecular sieve sample has an isolated silanol peak at a chemical shift of 1.8 ppm, and silanol peaks with hydrogen bonds between each other in the range of 2 to 6 ppm (2.2 ppm, 2.8 ppm, 3.8 ppm and 4.6 ppm, respectively). The peak areas of the above five peaks were calculated by integration and were: A1 = 18391, A2 = 13451, A3 = 25273, A4 = 23088 and A5 = 23459. The X3 values ​​calculated by formula (3) are listed in Table 3.

[0207] SEM images of sample CAT-1 are as follows: Figure 7 As shown in the figure, the molecular sieve consists of uniform ellipsoidal particles.

[0208] BET of sample CAT-1 Figure 8 As shown, there is a clear hysteresis loop between the nitrogen adsorption and desorption curves, and the initial relative pressure (P / P0) at which the hysteresis loop appears is 0.45.

[0209] Preparation of Comparative Example 1

[0210] The preparation of this comparative example follows the method of Preparation Example 1, except that no silanizing agent or structural filler is added. The resulting product is denoted as D-1. The preparation conditions are listed in Table 1, and the characterization results of the obtained molecular sieve are listed in Tables 2 and 3.

[0211] Preparation of Comparative Example 2

[0212] This comparative example was prepared using existing methods to prepare conventional titanium-silicon molecular sieves (Zeolites, 1992, Vol. 12, pp. 943-950).

[0213] 22.5 g of tetraethyl silicate and 7.0 g of tetrapropylammonium hydroxide were mixed, and 59.8 g of deionized water was added and mixed thoroughly. The mixture was then hydrolyzed at 60 °C for 1.0 h to obtain a hydrolyzed solution of tetraethyl silicate. A solution consisting of 1.1 g of tetrabutyl titanate and 5.0 g of isopropanol was then slowly added dropwise to this solution under vigorous stirring. The mixture was stirred at 75 °C for 3 h to obtain a clear and transparent colloid. This colloid was then transferred to a sealed stainless steel reactor and crystallized at 170 °C for 3 days to obtain conventional TS-1 molecular sieve, denoted as D-2. The preparation conditions are listed in Table 1, and the characterization results of the obtained molecular sieve are listed in Tables 2 and 3.

[0214] Preparation of Comparative Example 3

[0215] This comparative example was prepared according to the method of comparative example 2, except that a silanizing agent and a structural filler were added. The specific steps included are as follows:

[0216] (1) Mix 22.5g of tetraethyl silicate with 7.0g of tetrapropylammonium hydroxide, add 59.8g of deionized water and mix evenly; then hydrolyze at 60℃ for 1.0h to obtain a hydrolyzed solution of tetraethyl silicate. Then, under vigorous stirring, slowly add a solution composed of 1.1g of tetrabutyl titanate and 5.0g of isopropanol to the above solution, and stir the mixture at 75℃ for 3h to obtain a clear and transparent colloid.

[0217] (2) Add 1.9g of N-phenyl-3-aminopropyltrimethoxysilane (PHAPTMS) and 0.65g of PEO-PPO-PEO triblock copolymer (P123, purchased from Inokai, weight average molecular weight 5800) to the mixture in step (1) and stir for 2 hours.

[0218] (3) The colloid is then transferred to a stainless steel sealed reactor and crystallized at 170°C for 3 days to obtain the expanded-pore TS-1 molecular sieve, denoted as D-3. The preparation conditions are shown in Table 1, and the characterization results of the obtained molecular sieve are shown in Tables 2 to 3.

[0219] Preparation Examples 2-9

[0220] Multi-level porous titanium-silicon molecular sieves were prepared according to the method of Preparation Example 1, except that the ratio and synthesis conditions were changed to obtain multi-level porous titanium-silicon molecular sieve samples denoted as CAT-2 to CAT-9; the preparation conditions are listed in Table 1, and the characterization results of the obtained molecular sieves are listed in Tables 2 and 3.

[0221] Preparation Example 10

[0222] Multi-level porous titanium-silicon molecular sieves with MEL structures were prepared according to the method of Preparation Example 1. The difference from Preparation Example 1 was that the template agent was changed; tetrabutylammonium hydroxide (TBAOH) was used instead. The resulting multi-level porous titanium-silicon molecular sieve sample was designated CAT-10. The preparation conditions are listed in Table 1, and the characterization results of the obtained molecular sieve are listed in Tables 2 and 3. The XRD pattern of CAT-10 is shown in Tables 2 and 3. Figure 10 As shown, this indicates that CAT-10 is a MEL structure.

[0223] Preparation Example 11

[0224] Hierarchical porous β-zeolite was prepared according to the method of Preparation Example 1, except that the ratio and template agent were changed. Tetraethylammonium hydroxide (TEAOH) was used as the template agent to prepare a BEA topology, resulting in a hierarchical porous titanium silicate zeolite sample designated CAT-11. The preparation conditions are listed in Table 1, and the characterization results of the obtained zeolite are listed in Tables 2 and 3. The XRD pattern of CAT-11 is shown below. Figure 11 As shown, this indicates that CAT-11 is a BEA structure.

[0225] Preparation Example 12

[0226] The hierarchical porous titanium-silicon molecular sieve was prepared according to the method of Preparation Example 1, but the difference from Preparation Example 1 is as follows:

[0227] The temperature of the first hydrothermal crystallization treatment was 130℃ and the time was 96h; the temperature of the first calcination treatment was 350℃ and the time was 8h.

[0228] The second hydrothermal crystallization treatment was carried out at a temperature of 130℃ for 96 hours; the second calcination treatment was carried out at a temperature of 350℃ for 8 hours.

[0229] The obtained multi-level porous titanium silicate molecular sieve sample is designated as CAT-12; the characterization results of the obtained molecular sieve are listed in Tables 2 and 3.

[0230] Table 1

[0231]

[0232]

[0233] In Table 1, TPAOH is tetrapropylammonium hydroxide, TBAOH is tetrabutylammonium hydroxide, and TEAOH is tetraethylammonium hydroxide; PHAPTMS is N-phenyl-3-aminopropyltrimethoxysilane, APTMS is 3-aminopropyltriethoxysilane, GCPMS is 3-epoxypropoxypropyl(dimethoxy)methylsilane, and TOMS is methyltrimethoxysilane; P123 is PEO-PPO-PEO triblock copolymer, and CTAB is hexadecyltrimethylammonium bromide. The reagents used in this disclosure can be obtained through conventional purchasing channels. The water in the "water / silicon source" calculation in Table 1 also includes water from the aqueous solution of the first template agent; the water in the "water / molecular sieve intermediate" calculation also includes water from the aqueous solution of the second template agent.

[0234] Table 2

[0235]

[0236]

[0237] Table 3

[0238]

[0239] Reaction Example 1

[0240] This reaction example is used to illustrate the reaction effect of the method provided in this disclosure for amide alkylation.

[0241] The samples prepared in the above preparation examples and comparative examples were used as catalysts for the methylation of caprolactam to N-methylcaprolactam. The evaluation apparatus was an atmospheric pressure continuous flow fixed-bed reactor with an inner diameter of 5 mm and a catalyst loading of 2 g. After loading the catalyst, it was pretreated for 3 hours under a nitrogen atmosphere at atmospheric pressure and 350 °C. The concentration of the feed caprolactam was 10% by weight, and the solvent was methanol (hydrocarbon alcohol; the molar ratio of methanol to caprolactam was 1:8). The reaction conditions included a caprolactam weight hourly space velocity (WHSV, caprolactam flow rate in feed / catalyst weight in reactor) of 1 h⁻¹. -1 The reaction temperature was 380℃, the reaction pressure was 0.6MPa, the nitrogen flow rate was 4 L / h, and the reaction time was 12 h. The same catalytic reaction was then repeated 10 times using the same catalyst.

[0242] The reaction products were collected after cooling, and the concentrations of each substance were quantitatively analyzed by gas chromatography. An Agilent 6890 gas chromatograph with an HP-5 column was used. The test conditions included: vaporization chamber temperature 250℃, detection chamber temperature 230℃, and a programmed column temperature ramp: 110℃ for 8 minutes, ramped to 230℃ at a rate of 15℃ / min, and then held for 14 minutes. The results are shown in Table 4.

[0243] Wherein, caprolactam conversion rate % = (moles of caprolactam in the raw material - moles of caprolactam in the product) / moles of caprolactam in the raw material × 100%;

[0244] N-methylcaprolactam selectivity % = (moles of N-methylcaprolactam in the product) / (moles of caprolactam in the feed - moles of caprolactam in the product) × 100%;

[0245] The percentage decrease in caprolactam conversion rate = (caprolactam conversion rate after one reaction - caprolactam conversion rate after ten reactions) / caprolactam conversion rate after one reaction × 100%;

[0246] The decrease in N-methylcaprolactam selectivity = (N-methylcaprolactam selectivity after 1 reaction - N-methylcaprolactam selectivity after 10 reactions) / N-methylcaprolactam selectivity after 1 reaction × 100%.

[0247] Table 4

[0248]

[0249]

[0250] According to the data in Table 4 above:

[0251] Compared with the molecular sieves D-1 to D-3 prepared using Comparative Examples 1 to 3, the molecular sieves CAT-1 to CAT-12 provided in this disclosure exhibit higher caprolactam conversion and N-methylcaprolactam selectivity in the amide alkylation reaction. Furthermore, the decrease rate of caprolactam conversion and N-methylcaprolactam selectivity is smaller when the reaction is repeated multiple times, indicating that the catalyst used in the method provided in this disclosure has better resistance to deactivation and higher catalytic stability.

[0252] Comparing Preparation Example 1 with Preparation Example 9, Preparation Example 1 prepared molecular sieves according to the raw material addition ratio in the preferred embodiment. The resulting molecular sieve CAT-1 had higher caprolactam conversion and N-methylcaprolactam selectivity in the catalytic reaction, and the catalyst had better resistance to deactivation and higher catalytic stability.

[0253] Comparing Preparation Example 1 with Preparation Example 12, Preparation Example 1 prepared molecular sieves according to the reaction conditions in the preferred embodiment. The obtained molecular sieve CAT-1 had higher caprolactam conversion and N-methylcaprolactam selectivity in the catalytic reaction, and the catalyst had better resistance to deactivation and higher catalytic stability.

[0254] Comparative Example 1

[0255] This comparative example uses the method disclosed in existing technology CN102241614A to perform an amide alkylation reaction to obtain N-alkylamide compounds, specifically including:

[0256] (1) Weigh 1.0g of phosphotungstic acid, add 20mL of deionized water to dissolve it, then add 2.0g of MCM-41 molecular sieve, stir mechanically for one hour, let it stand and soak overnight; dry at 100℃ to remove moisture, activate at 300℃ for 4h, cool to room temperature, grind and use.

[0257] (2) Weigh 11.1 g of methanol, 2.1 g of caprolactam, 3.0 g of supported phosphotungstic acid catalyst, and 15.4 g of glacial acetic acid. Heat to 60 °C and reflux for 6.5 h; stop heating, let stand to room temperature, filter, and recover the catalyst; caprolactam conversion rate 80 mol%, N-methylcaprolactam selectivity 83 mol%.

[0258] Comparing reaction comparison example 1 with reaction example 1, it can be seen that the method provided in this disclosure can achieve higher raw material conversion rate and reaction product selectivity.

[0259] Reaction Examples 2-4

[0260] This reaction example illustrates the effect of the method provided in this disclosure on amide alkylation reactions under different reaction conditions.

[0261] The same reaction apparatus as in Reaction Example 1 was used, except that the reaction conditions were changed and the catalytic reaction was carried out according to the reaction conditions listed in Table 5 below. The reaction results are listed in Table 6.

[0262] Table 5

[0263]

[0264] Table 6

[0265]

[0266]

[0267] Based on the data in Tables 5 and 6, it can be seen that:

[0268] In reaction examples 2 and 3, different types of amide compounds and hydrocarbon alcohol compounds were used, and high conversion rates of amide compounds and N-hydroalkyl amide selectivity were obtained, indicating that the method provided in this disclosure has wide applicability to a variety of amide compounds and hydrocarbon alcohol compounds.

[0269] Comparing Reaction Example 4 with Reaction Example 1, it can be seen that when CAT-1 is used as the catalyst, Reaction Example 1 follows the following conditions: reaction temperature 350–400°C; reaction time 10–24 h; reaction pressure 0.1–2 MPa; and weight hourly space velocity of the amide compound 0.3–12 h⁻¹. -1 The reaction was carried out under the reaction conditions of "the molar ratio of hydrocarbon alcohols to amides is 1:(10-50)". The amides obtained in reaction example 1 had higher conversion rate and N-hydroalkyl amide selectivity.

[0270] The preferred embodiments of this disclosure have been described in detail above. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.

[0271] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.

[0272] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.

Claims

1. A method for N-alkylation, characterized in that, Includes the following steps: N-alkylation reaction is carried out by contacting amide compounds and hydrocarbon alcohols with a catalyst; The catalyst is a hierarchical porous titanium-silicon molecular sieve; the hierarchical porous titanium-silicon molecular sieve has multiple cavity structures within its crystals; The amide compound is selected from one or more of butyrolactam, valproic acid lactam, caprolactam, heptanolactam, octylolactam, and laurylolactam; the hydrocarbon group in the hydrocarbon alcohol has 1 to 8 carbon atoms. The multi-level porous titanium-silicon molecular sieve has the following characteristics: 31 P MAS NMR characteristics: The peak intensity of the characteristic peak at a chemical shift of -6±1ppm of the hierarchical porous titanium-silicon molecular sieve is denoted as N1; the peak intensity of the characteristic peak at a chemical shift of -34±1ppm of the hierarchical porous titanium-silicon molecular sieve is denoted as N2; and the peak intensity of the characteristic peak at a chemical shift of -61±1ppm of the hierarchical porous titanium-silicon molecular sieve is denoted as N3. X 1-1 =N1 / N3 (1-1); and X 1-2 =N2 / N3 (1-2); The X 1-1 X is any value between 0.18 and 0.29; 1-2 It can be any value between 0.12 and 0.20; The multi-level porous titanium-silicon molecular sieve has the following characteristics: 29 Si MAS NMR characteristics: The peak area of ​​the spectral peak at the position where the chemical shift of the molecular sieve is -103±1ppm is denoted as Q. 3 The peak area of ​​the spectral peak at the position where the chemical shift of the molecular sieve is -113±1ppm is denoted as Q. 4-1 The peak area of ​​the spectral peak at the position where the chemical shift of the molecular sieve is -116±1ppm is denoted as Q. 4-2 ; X 2-1 =Q 3 / Q 4-1 Equation (2-1); X 2-2 =Q 3 / Q 4-2 Equation (2-2); X 2-1 X is any value between 0.08 and 0.

28. 2-2 It can be any value between 0.25 and 0.48; The hierarchical porous titanium-silicon molecular sieve is prepared by a method including the following steps: S1. Mix the titanium source, silicon source, first template agent, water, silanizing agent and structural filler to obtain a reaction mixture; S2. The reaction mixture is subjected to a first hydrothermal crystallization treatment and a first calcination treatment in sequence to obtain a molecular sieve intermediate; S3. Mix the molecular sieve intermediate, the second template agent and water, and then perform the second hydrothermal crystallization treatment and the second calcination treatment in sequence. The silanizing agent is N-phenyl-3-aminopropyltrimethoxysilane, the structural filler is a PEO-PPO-PEO block copolymer, the silicon source is an organosilicon ester, the titanium source is a titanium-containing organic acid ester, and the first template agent and the second template agent are quaternary ammonium bases.

2. The method according to claim 1, characterized in that, The hydrocarbon alcohol is selected from one or more of methanol, ethanol, propanol, butanol and hexanol.

3. The method according to claim 1, characterized in that, The conditions for the N-alkylation reaction include: a reaction temperature of 200–450 °C; a reaction time of 1–72 h; a reaction pressure of 0.1–3 MPa; and a weight hourly space velocity (WHSV) of 0.2–15 h⁻¹ for the amide compound. -1 The molar ratio of the amide compound to the hydrocarbon alcohol is 1:(3~100).

4. The method according to claim 3, characterized in that, The conditions for the N-alkylation reaction include: a reaction temperature of 350–400 °C; a reaction time of 10–24 h; a reaction pressure of 0.1–2 MPa; and a weight hourly space velocity (WHSV) of 0.3–12 h⁻¹ for the amide compound. -1 The molar ratio of the amide compound to the hydrocarbon alcohol is 1:(10~50).

5. The method according to claim 1, characterized in that, The reactor for the N-alkylation reaction is selected from any one of a fixed-bed reactor, a batch reactor, a moving-bed reactor, a suspended-bed reactor, or a slurry-bed reactor.

6. The method according to claim 1, characterized in that, The size of a single cavity structure in the multi-level porous titanium-silicon molecular sieve is 2~50nm; The volume of all the aforementioned cavity structures accounts for 10-50% of the total volume of the molecular sieve; The shape of the cavity structure is selected from one or more of the following: sphere, cube, ellipsoid, and irregular cube.

7. The method according to claim 6, characterized in that, The size of a single cavity structure in the multi-level porous titanium-silicon molecular sieve is 5~40nm; The volume of all the cavity structures described accounts for 15-45% of the total volume of the molecular sieve.

8. The method according to claim 1, characterized in that, The multi-level porous titanium-silicon molecular sieve has the following characteristics: 1 H MASNMR characteristics: The peak area at the chemical shift position of 1.8±0.1ppm is denoted as A1, the peak area at the chemical shift position of 2.2±0.1ppm is denoted as A2, the peak area at the chemical shift position of 2.8±0.1ppm is denoted as A3, the peak area at the chemical shift position of 3.8±0.1ppm is denoted as A4, and the peak area at the chemical shift position of 4.6±0.1ppm is denoted as A5. As defined in equation (3), X3 is any value between 0.2 and 0.9: X3=A1 / (A2+A3+A4+A5) equation (3).

9. The method according to claim 1, characterized in that, The molar ratio of silicon atoms to titanium atoms in the multi-level porous titanium-silicon molecular sieve is (10~100):

1.

10. The method according to claim 9, characterized in that, The molar ratio of silicon atoms to titanium atoms in the multi-level porous titanium-silicon molecular sieve is (15~80):

1.

11. The method according to claim 1, characterized in that, The multi-level porous titanium-silicon molecular sieve is selected from one or more of the following molecular sieve structures: MFI, MEL, BEA, MWW, two-dimensional hexagonal, MOR, and TUN.

12. The method according to claim 1, characterized in that, The multi-level porous titanium-silicon molecular sieve is selected from one or more of the following molecular sieve structures: MFI, MEL, BEA, MCM, and SBA.

13. The method according to claim 1, characterized in that, The multi-level porous titanium-silicon molecular sieve includes molecular sieve particles composed of single crystals, and / or molecular sieve particles composed of aggregates of multiple crystals. The molecular sieve particles have an average particle size of 0.1~0.8μm and a BET specific surface area of ​​250~650m². 2 / g; Microporous specific surface area is 280~550m² 2 / g; total pore volume is 0.2~0.55cm³. 3 / g; mesopore volume is 0.1~0.4cm³ 3 / g; There is a hysteresis loop between the adsorption isotherm and desorption isotherm of the low-temperature nitrogen adsorption of the multi-level porous titanium-silicon molecular sieve.

14. The method according to claim 13, characterized in that, The molecular sieve particles have an average particle size of 0.15~0.65μm and a BET specific surface area of ​​280~600m². 2 / g; microporous specific surface area is 300~500m² 2 / g; total pore volume is 0.25~0.54cm³. 3 / g; mesopore volume is 0.15~0.35cm³ 3 / g.

15. The method according to claim 13, characterized in that, The initial relative pressure at which the hysteresis loop appears is 0.3~0.

55.

16. The method according to claim 1, characterized in that, In step S1, the molar ratio of titanium source: silicon source: first template agent: water: silanizing agent is (0.002~0.15):1:(0.01~4):(1~50):(0.02~0.35); the weight ratio of SiO2 to structural filler in the reaction mixture is (5~50):

1.

17. The method according to claim 16, characterized in that, In step S1, the molar ratio of titanium source: silicon source: first template agent: water: silanizing agent is (0.01~0.06):1:(0.02~1.5):(10~30):(0.03~0.15); the weight ratio of SiO2 to structural filler in the reaction mixture is (8~30):

1.

18. The method according to claim 1, characterized in that, In step S1, the organosilicon ester has the general formula shown in formula (A): (A); Where R a R b R c R d Each is independently selected from alkyl groups having 1 to 6 carbon atoms, wherein the alkyl group is a branched or straight-chain alkyl group.

19. The method according to claim 18, characterized in that, R a R b R c R d Each is independently selected from straight-chain alkyl groups having 1 to 4 carbon atoms or branched alkyl groups having 3 to 4 carbon atoms.

20. The method according to claim 19, characterized in that, The R a R b R c R d Each is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, or tert-butyl.

21. The method according to claim 1, characterized in that, The organosilicon ester is selected from one or more of tetramethyl silicate, tetraethyl silicate, tetrabutyl silicate, and dimethyl diethylsilyl ester.

22. The method according to claim 1, characterized in that, The first and second template agents are each independently selected from at least one of quaternary ammonium bases having the structure shown in formula (B): (B); R1, R2, R3 and R4 are each selected from alkyl groups having 1 to 4 carbon atoms.

23. The method according to claim 22, characterized in that, R1, R2, R3 and R4 are each one or more of straight-chain alkyl groups having 1 to 4 carbon atoms and branched alkyl groups having 3 to 4 carbon atoms.

24. The method according to claim 23, characterized in that, R1, R2, R3 and R4 are each selected from one or more of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl and tert-butyl.

25. The method according to claim 1, characterized in that, The first template agent and the second template agent are each independently tetrapropylammonium hydroxide or a mixture of tetrapropylammonium hydroxide and one or more selected from tetrapropylammonium chloride and tetrapropylammonium bromide.

26. The method according to claim 1, characterized in that, The titanium-containing organic ester is selected from at least one of the structures represented by the general formula (C): (C); R5, R6, R7 and R8 are each selected from alkyl groups having 1 to 6 carbon atoms.

27. The method according to claim 26, characterized in that, R5, R6, R7 and R8 are each selected from straight-chain alkyl groups having 1 to 4 carbon atoms and branched alkyl groups having 3 to 6 carbon atoms.

28. The method according to claim 27, characterized in that, R5, R6, R7 and R8 are each selected from straight-chain alkyl groups having 2 to 4 carbon atoms and branched alkyl groups having 2 to 4 carbon atoms.

29. The method according to claim 28, characterized in that, R5, R6, R7 and R8 are each selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, isopentyl, hexyl or isohexyl.

30. The method according to claim 1, characterized in that, The titanium source is selected from one or more of tetraethyl titanate, tetrapropyl titanate, and tetrabutyl titanate.

31. The method according to claim 1, characterized in that, Step S1 includes: a. Mix titanium source, silicon source, first template agent and water to obtain silicon hydrolysis sol; b. Add the silanizing agent and the structural filler to the hydrolyzed silicon sol, respectively, and mix to obtain the reaction mixture; The mixing conditions in step a include stirring at 40~90℃ for 6~12 hours; The mixing conditions in step b include stirring at 20~50℃ for 2~4 hours.

32. The method according to claim 1, characterized in that, In step S3, the weight ratio of the second template agent: water: molecular sieve intermediate is (0.2~3.5):(2~50):

1.

33. The method according to claim 32, characterized in that, In step S3, the weight ratio of the second template agent: water: molecular sieve intermediate is (0.25~2.2):(3~35):

1.

34. The method according to claim 1, characterized in that, The conditions for the first hydrothermal crystallization treatment in step S2 and the second hydrothermal crystallization treatment in step S3 each independently include: hydrothermal crystallization time of 6~168h, hydrothermal crystallization temperature of 130~200℃; and pressure of autogenous pressure. The conditions for the first roasting treatment in step S2 and the second roasting treatment in step S3 each independently include: a roasting temperature of 300~700℃ and a roasting time of 1~16h.

35. The method according to claim 34, characterized in that, The conditions for the first hydrothermal crystallization treatment in step S2 and the second hydrothermal crystallization treatment in step S3 each independently include: hydrothermal crystallization time of 24~72h, hydrothermal crystallization temperature of 150~180℃; and pressure of autogenous pressure. The conditions for the first roasting treatment in step S2 and the second roasting treatment in step S3 each independently include: a roasting temperature of 400~600℃ and a roasting time of 2~5h.

Citation Information

Patent Citations

  • Synthesis method of N-alkyl-substituted amide compounds

    CN102241614A

  • Production method of titanium-silicon molecular sieve, titanium-silicon molecular sieve produced by method, and ammoximation reaction method

    CN109721065A

  • MFI molecular sieve and preparation method thereof, and caprolactam preparation method

    CN114349018A